2012
DOI: 10.1007/s11064-012-0857-3
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Short Chain Fatty Acid Transport by Members of the Monocarboxylate Transporter Family (MCT)

Abstract: Metabolism of short-chain fatty acids (SCFA) in the brain, particularly that of acetate, appears to occur mainly in astrocytes. The differential use has been attributed to transport, but the extent to which transmembrane movement of SCFA is mediated by transporters has not been investigated systematically. Here we tested the possible contribution of monocarboxylate transporters to SCFA uptake by measuring fluxes with labelled compounds and by following changes of the intracellular pH in Xenopus laevis oocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 33 publications
1
45
0
Order By: Relevance
“…Here, we observed that acetate induces expression of both MCT1 and MCT4 over time, without changes in the levels of GLUT1, the main glucose transporter expressed in CRC [16, 41, 47]. Furthermore, upon acetate treatment, we observed an increase in glucose consumption and lactate production up to 24h in CRC cells, which goes in line with the increased expression of MCTs and the need to export the produced lactate [4851]. Our findings are in agreement with Matthews et al , describing that butyrate and propionate, alone or in combination, significantly increased glucose consumption.…”
Section: Discussionmentioning
confidence: 52%
“…Here, we observed that acetate induces expression of both MCT1 and MCT4 over time, without changes in the levels of GLUT1, the main glucose transporter expressed in CRC [16, 41, 47]. Furthermore, upon acetate treatment, we observed an increase in glucose consumption and lactate production up to 24h in CRC cells, which goes in line with the increased expression of MCTs and the need to export the produced lactate [4851]. Our findings are in agreement with Matthews et al , describing that butyrate and propionate, alone or in combination, significantly increased glucose consumption.…”
Section: Discussionmentioning
confidence: 52%
“…27 SCFA can be absorbed through the apical membrane of colonic epithelial cells via four putative mechanisms: non-ionic diffusion of protonated SCFA; 40 exchange with bicarb onate in a ratio of 1:1; 41 via the hydrogen-coupled monocarboxylate transporter 1 (MCT 1), MCT 2 and MCT 4; 42,43 and via sodium-coupled monocarboxylate transporter 1. 43 SCFA absorbed in the caecum, ascending colon or transverse colon are transported into the superior mesenteric vein, whilst SCFA absorbed in the descending colon and sigmoid enter the inferior mesenteric vein, which both drain into the portal vein and liver. 44,45 Interestingly, SCFA absorbed in the sigmoid and rectal region can also bypass the liver via the pelvic plexus, which drains into the inferior vena cava, thereby reaching the systemic circulation directly.…”
Section: Scfa Absorption and Systemic Concentrationsmentioning
confidence: 99%
“…While other mechanisms are also possible (Dikicioglu et al, 2014), the ABC transporter (Sá-Correia et al, 2009) Pdr18 (Teixeira et al, 2012) and the glyceroaquaporin Fps1 (Teixeira et al, 2009) have properties consistent with such a role as ethanol transporters in yeast, a fact of considerable biotechnological relevance (Dunlop et al, 2011). In the context of biofuels production (and ethanol is a biofuel), and based on similar strategies of toxicity resistance to the one that we exploited earlier (Lanthaler et al, 2011), we now also know them for a variety of other rather lipophilic substances such as alkanes (Tsukagoshi and Aono, 2000; Fernandes et al, 2003; Ankarloo et al, 2010; Chen et al, 2013; Doshi et al, 2013; Foo and Leong, 2013; Ling et al, 2013; Nishida et al, 2013), arenes (Kieboom et al, 1998b), terpenoids (Jasiński et al, 2001; Yazaki, 2006; Foo and Leong, 2013), long-chain fatty acids (Wu et al, 2006a,b; Khnykin et al, 2011; Lin and Khnykin, 2014; Villalba and Alvarez, 2014), short-chain fatty acids (Gimenez et al, 2003; Islam et al, 2008; Moschen et al, 2012; Sá-Pessoa et al, 2013), etc. These are all substances for which bilayer lipoidal diffusion was “once widely assumed” (and presumably still is in some quarters).…”
Section: Intellectual Challenges Around Bilayer Lipoidal Permeabilitymentioning
confidence: 99%